1984
DOI: 10.1063/1.447571
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and ionization energies of N–F and P–F compounds

Abstract: NF3, N2F4, NF2, PF3, P2F4, PF2, and PF2I have been studied by photoionization mass spectrometry. Modified or confirmatory values have been obtained for the heats of formation of NF+3, NF+2, and NF+ and the ionization potentials of NF3 and NF2. The stepwise bond energies are deduced to be D00(NF) =3.27±0.02 eV; D00(FN–F) =2.85±0.02 eV; and D00(F2N–F) =2.47±0.01 eV. Heats of formation at 0 K have been measured for PF+2 (89.6±0.5 kcal/mol), PF+ (≤214.8 kcal/mol), and PF2I (−142.3±1.0 kcal/mol). The directly measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 29 publications
8
17
0
Order By: Relevance
“…These ratios are uncorrected for the effects of instrumental discrimination against the more energetic fragment ions: as will be seen below this almost certainly leads to an underestimation of the abundance ofPF 2 + , by as much as a factor of2. With such a correction we find good agreement with the 58.4 nm photoionization abundances reported by Berkowitz et al 13 The low abundance of PF + at these photon energies is consistent with its reported (electron impact) appearance potential of about 20.5 eV.IO,12 crOF spectra were recorded with selected photoelectron energies throughout the photoelectron bands. Only the parent molecular ion, PF l; was observed in coincidence with X band photoelectrons; hence,· the ground state ion is stable with respect to dissociation.-In contrast, all excited states of the ion were observed to be fully and exclusively dissociated to PFl.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These ratios are uncorrected for the effects of instrumental discrimination against the more energetic fragment ions: as will be seen below this almost certainly leads to an underestimation of the abundance ofPF 2 + , by as much as a factor of2. With such a correction we find good agreement with the 58.4 nm photoionization abundances reported by Berkowitz et al 13 The low abundance of PF + at these photon energies is consistent with its reported (electron impact) appearance potential of about 20.5 eV.IO,12 crOF spectra were recorded with selected photoelectron energies throughout the photoelectron bands. Only the parent molecular ion, PF l; was observed in coincidence with X band photoelectrons; hence,· the ground state ion is stable with respect to dissociation.-In contrast, all excited states of the ion were observed to be fully and exclusively dissociated to PFl.…”
Section: Resultssupporting
confidence: 89%
“…10-12 More recently, analogous threshold values were determined by photoionization mass spectrometry. 13 There are, however, significant disagreements, both between the photon-and electron impact induced ionization studies, and between the various electron impact ionization studies themselves. Dynamical aspects of the PF 3 + molecular ion fragmentation process appear not to have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Table II contains the improved molecular constants for the d -a system, including the first values for vЈϭ4. Higher vibrational levels may well predissociate to ground state atomic fragments; the presence of the P( 4 S)ϩF( 2 P) dissociation limit between vϭ4 and 5 of the d state is entirely consistent with the D 0 value of 37 100Ϯ3500 cm Ϫ1 determined by Berkowitz et al 33 Figure 7 shows that the vibrational spacing in the d 1 ⌸ state increases in an even more pronounced fashion with v than that in the A 3 ⌸ state. As the two states arise from the same configuration, the d state potential may also be unusual.…”
Section: B the Da Band Systemsupporting
confidence: 85%
“…Berkowitz et al 16 established a value of 8.847±0.01 eV for the first IPa using photoionization mass spectrometry-a value supported by Butcher et al using conventional photoelectron spectroscopy (PES). 17,18 Calculations of the first IP a and of the geometry of the cation have also been reported.…”
Section: Introductionmentioning
confidence: 91%
“…Other demonstrated production routes include creating a dc discharge in PF 3 /Ar (Ref. 8) or PH 3 /CFiAr mixtures,7 high energy irradiation of PF 2 containing compounds such as PF 3 , 11,13 NH PF 10 P F 12,14 and PF H 12 and P F pyrolysis 12, 16 4 6, 2 4, 2 , 2 4 . In this paper we report the observation of nine new electronic states of PF 2 revealed via the two photon resonance enhancements they provide to the MPI spectrum of the radical.…”
Section: Introductionmentioning
confidence: 99%